The Dynamic of Women Entrepreneurs, Environmental Awareness, and Family Welfare: A Green Economy Perspective - Mirandha Ariesca Riana; Jannah, Mardiatul; Arizahni, Keisyah Rifqah; Sary , Cherry Arma (Universitas Muhammadiyah Sorong, 2025)
This study aims to analyze the impact of strengthening the potential of women entrepreneurs on family welfare, with environmental awareness as a moderating variable within the green economy perspective. An explanatory quantitative method was used, employing purposive sampling involving 200 women entrepreneurs in Indonesia engaged in sustainable business practices. Data were collected through surveys and analyzed using SmartPLS, including validity and reliability tests, classical assumption tests (multicollinearity, heteroscedasticity, normality), and moderated regression analysis. The findings indicate that strengthening the potential of women entrepreneurs has a positive and significant impact on family welfare, and environmental awareness enhances this relationship. The practical implications of this study highlight the importance of integrating sustainability values into women entrepreneurs’ empowerment to sustainably improve family welfare. The theoretical implications contribute to the literature on women’s entrepreneurship and the green economy. However, this study has limitations, as it does not measure other variables that may affect family welfare. Future research is recommended to include more contextual variables and involve a broader population.